Polyacrylamide-assisted combustion-carbothermal synthesis of well-distributed SiC nanowires. Issue 10 (December 2015) - Chu, Aimin; Zhang, Dezhi; Rafi-ud-din,; Guo, Shibo; Qu, Xuanhui
Abstract: SiC nanowires are produced by employing a novel synthesis process involving the carbothermal reduction reaction of Polyacrylamide (PAM)-assisted low-temperature combustion synthesis (LCS) precursors. PAM-assisted LCS mixtures with high specific surface area and fibers with various size are used as precursors. The precursors, derived from silicic acid (Si source), PAM (additive), nitric acid (oxidizer), urea (fuel), and glucose (C source) mixed solution, are prepared by PAM-assisted LCS method. The prepared precursors have exhibited a high contact area of reactants. The carbothermal reduction of these high specific surface area precursors results in the formation of pure and well-distributed SiC nanowires with a diameter of 50 nm and a length of up to several micrometers. The effects of PAM contents and carbothermal reduction parameters on the production of SiC nanowires are discussed in detail. The precursors and corresponding carbothermal reduction products are investigated by FESEM, TEM, HRTEM, and XRD analyses.